Perancangan Animasi Keris Berbasis Augmented Reality sebagai Sarana Pengembangan Hasil Kebudayaan Jawa dengan Media Baru - Anung Rachman; Rendya Adi Kurniawan; Isnawati Muslihah; Aufara Fiqi Fatahilah (DeKaVe, 2025)
When it comes to cultural richness, it can’t be denied that Indonesia has abundant amount of cultural products. As Indonesian citizens who love culture, the diversity of existing cultural products should always be preserved and developed in order to maintain the echo of the existence of a distinct culture. It goes well with a statement that says, “culture is a reflection of national character and identity”. Referring to the meaning of the word “preserve” whic is maintaining the philosophical values as they are in an existing culture, while “developing” in this context means taking the values from the original Indonesian culture and then combining them with new external elements without losing their very own characteristics. This scientific text explains the process of designing a short animation in the form of a keris which had been combined with a touch of fantasy, and then displayed using augmented reality (AR) system. This animation plays its role to developing one of the Javanese cultural product, especially keris, without losing the distinctive characteristics of the keris itself. In creating this animation, the author, who also acts as the animation designer, used Clip Studio Paint software to create visual assets for the animation, then converted it to GIF format using the Procreate appliacation, and finally imaged it in AR form using a software called Adobe Aero. The result of this series of processes is a QR code that can be scanned with a smart phone which will display a short animation of the keris itself in AR form. But, note that the audiences must first download Adobe Aero on their smart phone to watch the animation.